Can a simple trapezoidal integration approach accurately estimate the supra-critical speed distance capacity of a swimmer? - Bulte, K. R.; Mitchell, L. L. G.; Siegel, R.; Hunter, A.; Brooks, E. R.; Saunders, P. U.; Hoffmann, S. M. (International Journal of Sports Physiology and Performance, 2026)
The 12 × 25-m swim test has become a key physiological monitoring and profiling tool within swimming networks to capture various performance insights (peak velocity, critical speed [CS], supra-CS distance capacity [D'], and anaerobic speed reserve) within one testing occasion. The D' output following the 12 × 25-m swim test is currently derived using software that requires specialised expertise, therefore inhibiting the accessibility of the test to pathways` level coaches and athletes. Objectives: The aim of the study was to determine if trapezoidal integration (TI) could simply and accurately replace the model fit method to estimate D' following the 12 × 25-m swim test and improve the accessibility of the test for a wider cohort of practitioners. Methods: Thirty-one national-level swimmers preparing for the Paris 2024 Olympic Trials consented for their 12 × 25-m data set to be retrieved. D' was calculated using both the model fit and TI approaches. Linear regression and pearson correlations examined the strength of the relationship and a paired t test and Bland-Altman plot determined the agreement between the 2 methodologies. Results: A very strong, positive relationship was found between the model fit and TI D' calculations (r = .999, R2 = .999, P < .001), with a very small, nonsignificant difference of 0.040 m (d = 0.124, P = .495). Conclusions: TI is a valid replacement for the original model fit approach to estimate D' following the 12 × 25-m swim test. The swim test will no longer require specialised software and the accessibility of the test will increase to a wider cohort of swimming practitioners.